2016
DOI: 10.3390/ijms17121979
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Effect of Chakasaponins I and II, Floratheasaponin A, and Epigallocatechin 3-O-Gallate Isolated from Camellia sinensis on Human Digestive Tract Carcinoma Cell Lines

Abstract: Acylated oleanane-type triterpene saponins, namely chakasaponins I (1) and II (2), floratheasaponin A (3), and their analogs, together with catechins—including (–)-epigallocatechin 3-O-gallate (4), flavonoids, and caffeine—have been isolated as characteristic functional constituents from the extracts of “tea flower”, the flower buds of Camellia sinensis (Theaceae), which have common components with that of the leaf part. These isolates exhibited antiproliferative activities against human digestive tract carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…For instance, Theasaponin E 1 has been theorized as a possible cancer treatment option because of its anti-angiogenesis mechanisms [ 35 ]. Chakasaponins I and II and floratheasaponin A showed anti-proliferative activities through apoptotic-induced cell death by activation of caspase-3/7 in HSC-2 cells [ 38 ]. Little research has been published on tea saponins beneficial biological activities on ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Theasaponin E 1 has been theorized as a possible cancer treatment option because of its anti-angiogenesis mechanisms [ 35 ]. Chakasaponins I and II and floratheasaponin A showed anti-proliferative activities through apoptotic-induced cell death by activation of caspase-3/7 in HSC-2 cells [ 38 ]. Little research has been published on tea saponins beneficial biological activities on ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…TS has been demonstrated as being an excellent bio-surfactant with numerous pharmacological activities. TS has been documented as having gastroprotective [ 33 ], anti-fungal [ 34 ], anti-viral [ 25 ], anti-oxidative [ 24 ], anti-obesity [ 35 ], anti-inflammatory [ 24 , 28 ], anti-hyperglycemic [ 27 ], immunomodulatory [ 36 ], and anti-tumor [ 35 , 37 , 38 ] tendencies. However, unlike other phenolic compounds, EGCG [ 39 , 40 , 41 ] and TFs [ 37 , 42 ] separated from tea plants, TS has not been reported as having pharmacological influences on human ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Kitagawa et al showed that Chakasaponin I, II, and Floratheasaponin A have inhibitory effects on human gastrointestinal cancer cells HSC-2, HSC-4, MKN-45, and Caco-2, and the effect is stronger than catechin, flavonoids, and caffeine. The inhibition of HSC-2 cell proliferation may be due to the induction of cell cycle arrest in the G2/M phase and activation of apoptosis [16]. Previously, we also reported the effects of tea flower saponins containing Chakasaponin II and other 13 monomers on ovarian cancer cells; the results demonstrated that tea flower saponins shows strong anticancer activity by inducing apoptosis and S phase cell cycle arrest in human OVCAR-3 and A2780/CP70 cancer cells [17].…”
Section: Introductionmentioning
confidence: 84%
“…We previously identified 21 triterpenoid saponins in extracts from tea flowers in selected cultivars [23]. In recent years, the bio-functional effects of tea flower saponins such as antihyperlipidemic, antihyperglycemic, anti-obesity, anti-cancer, and gastroprotective effects have been reported [24][25][26], among which Chakasaponin I has been reported to have antihyperlipidemic and antihyperglycemic [27], anti-cancer [26], and anti-obesity [28] effects. We previously reported that tea flower saponins containing 14 triterpenoid saponins could induce cell cycle arrest and apoptosis in human ovarian cancer cells [29].…”
Section: Introductionmentioning
confidence: 99%